Influence of Time-of-Day on Maximal Exercise Capacity Is Related to Daily Thermal Balance but Not to Induced Neuronal Activity in Rats - Machado, Frederico S. M.; Fóscolo, Daniela R. C.; Poletini, Maristela O.; Coimbra, Cândido C. (Frontiers in Physiology, 2016)
In the present study, we investigated whether the daily fluctuations of internal body temperature (Tb) and spontaneous locomotor activity (SLA) interact with the thermal and neuronal adjustments induced by high-intensity aerobic exercise until fatigue. The body temperature and SLA of adult Wistar rats (n = 23) were continuously recorded by telemetry for 48 h. Then, the rats were subjected to a protocol of graded exercise until fatigue or rest on the treadmill during light and dark-phases. Tb, tail skin temperature and ambient temperature during each experimental session were recorded. At the end of the last experimental session, the animals were anaesthetized; the brains were perfused and removed for immunohistochemical analysis of c-fos neuronal activation. The daily rhythms of SLA and Tb were strongly correlated (r = 0.88 and p < 0.001), and this was followed by a daily oscillation in both the ratio and the correlation index between these variables (p < 0.001). Exercise capacity was associated with a lower resting Tb (p < 0.01) and was higher in the light-phase (p < 0.001), resulting in an increased capacity to accumulate heat during exercise (p < 0.01). Independent of time-of-day, high intensity exercise strongly activated the hypothalamic paraventricular nucleus (PVN), the supra-optic nucleus (SON) and the locus coeruleus (LC) (p < 0.001) but not the suprachiasmatic nucleus (SCN). Taken together, our results points toward a role of the circadian system in a basal activity control of the thermoregulatory system as an important component for the onset of physical activities. In fact, rather than directly limiting the adjustments induced by exercise the present study brings new evidence that the effect of time-of-day on exercise performance occurs at the threshold level for each thermoregulatory system effector activity. This assumption is based on the observed resilience of the central clock to high-intensity exercise and the similarities in exercise-induced neuronal activation in the PVN, SON, and LC.